Islamic Education Teacher Communication Strategy in Increasing Students 'Learning Interest - Amiruddin Amiruddin; Nurdin Nurdin; Moh. Ali (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2021)
This paper discusses the forms of academic communication of Islamic religious education teachers in Improving Student Learning Interest in Limua Dapurang Elementary School, Dapurang District, Pasangkayu Regency. This study used a case study approach. Data collection techniques in this study using observation, interviews and documentation. Data analysis techniques through data reduction analysis, data presentation and data verification that ends with checking the validity of the data with the source triangulation method. The results showed that the forms of Academic communication of Islamic education teachers in increasing the learning interest of the students regarding interpersonal communication which includes approaching, giving advice, exemplary, and reward. Second, group communication includes explaining the material gently, decisively and attractively, motivating and increasing the activeness of students and providing habituation. The results of increasing students' interest in learning caused students doing assignment diligently, hard studying, and increase student grades. The supporting factors include the teacher's ability to communicate, a willingness of students to receive advice and the support of class teachers. While the inhibiting factors are the level of understanding and response power of students and the lack of support from parents.